Test of the Anti-Inflammatory Effectiveness of Ethanol Extract Gel Preparation of Sabrang Onion Bulb (Eleutherine bulbosa) on Incisional Wounds in Wistar Rats - Harahap, Hasni Yaturramadhan; Syarifuddin, Shofian; Cahya, Cucu Arum Dwi; Br Sinaga, Irma Suryani Kristina (Jurnal FARMASIMED (JFM), 2024)
Background: The use of medicinal plants is increasingly widespread among the community, especially due to their properties in healing various diseases. One of the developing medicinal plants is bawang sabrang (Eleutherine bulbosa), which has been proven to accelerate the healing process of wounds. Objective: To evaluate the effectiveness of administering gel extract from bawang dayak tubers on the healing process of incised wounds in rats. The test subjects used were 25 male rats. Incisions measuring 2 cm were made on the backs of the rats using a surgical knife. Method: Laboratory experimental study with a Completely Randomized Design (CRD) consisting of five treatments: one positive control (bioplacenton gel), one negative control (gel base), and three graduated concentrations of gel extract, namely 5%, 10%, and 15%. Treatments were administered twice daily for 14 days. Results: Measurement of wound diameter showed that the gel extract of bawang sabrang at a concentration of 15% and the positive control provided a more effective healing effect compared to the gel extract at concentrations of 5%, 10%, and the negative control (gel base). Conclusion: Ethanol extract of bawang sabrang is effective as a gel for healing incised wounds in rats at a concentration of 15%. The physical properties of the gel show a characteristic aroma and a golden red color, homogenous without grains or lumps, a pH of 4.9, and a spreadability of 5 cm.Keywords: Bawang sabrang tuber, Anti-inflammatory, rats, Edema.